Differences in pain, disability, and psychological function in low back pain patients with and without anxiety - Jiang, Ying; Wang, Yizu; Wang, Rui; Zhang, Xiaogang; Wang, Xueqiang (Frontiers in Physiology, 2022)
Objectives: low back pain is a very common cause of musculoskeletal disorders which leads disability, work reduced hours and the need for rehabilitation. The aim of this study was to evaluate whether there were differences in pain, dysfunction and psychological factors between the two groups. Supplementary demonstrated the relationship between these influencing factors and anxiety. Methods: a cross-sectional study was designed to analysis the differences in pain, disability and psychological function in LBP patients with and without anxiety. 60 participants were needed to complete study, Classified the participants into two groups by self-rating anxiety. The pain intensity was assessed by Visual Analog Scale, Psychological function including Pain Anxiety Symptoms Scale, Tampa Scale for Kinesiophobia and The Fear Avoidance Beliefs Questionnaire, functional disability using The Oswestry Disability Index and Roland Morris Disability Questionnaire, quality of life using 36-Item Short Form Health Survey questionnaire and quality of sleep using Pittsburgh Sleep Quality Index, the relationships between variables and anxiety scores were estimated by spearman correlation analysis. Results: total 60 participants were enrolled after self-rating anxiety assessed and finished the full investigation. The analyses showed significant differences of pain intensity, disability and psychological function between 2 groups. Spearman correlation analysis showed that anxiety score had significant positive correlations with functional disability, psychological function, and excellent positive correlation with quality of sleep, strongly negative correlations with quality of life. Conclusions: we recognized that anxiety in low back pain patients was interaction with by intensity of pain, disability level and a mass of psychological function.